Autoimmune Encephalitis With Multiple Auto-Antibodies With Concomitant Human Herpesvirus-7 and Ovarian Teratoma: A Case Report - Yang, Jianhua; Wu, Pengcheng; Liu, Xianghong; Xia, Han; Lai, Zhaohui (Frontiers in Medicine, 2022)
Infectious etiologies and tumors are common triggers of autoimmune encephalitis. We herein reported a rare case of autoimmune encephalitis with multiple auto-antibodies in CSF and serum, with concomitant human herpes virus 7 (HHV-7) infection and ovarian teratoma. A 36-year-old woman presented with mental and behavioral changes and gibberish for 13 days, followed by fever for 1 day. Her brain magnetic resonance imaging (MRI) indicated limbic encephalitis. Metagenomic next-generation sequencing (mNGS) of cerebrospinal fluid (CSF) revealed HHV-7. Antibody testing showed positive anti-N-methyl-D-aspartate receptor (NMDAR) and anti-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor(AMPAR) antibodies in CSF and serum. Ovarian teratoma was considered after pelvic MRI, which was then confirmed pathologically after laparoscopic ovariectomy. Her conditions improved after laparoscopic surgery, intravenous steroids, immunoglobulin, and rituximab therapy. Our findings suggested that the combination of multiple therapies including antiviral, immunotherapy, and resection of tumors were appropriate and improved prognosis when HHV-7 infection and ovarian teratoma was concomitant with multiple anti-neuronal antibodies of autoimmune encephalitis.